Center-Pivot-Irrigated Soybean Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J. (My University, 1999)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated soybean production in Kansas.
MF586_1999_10
Keywords: MF586; Economics; Crops; MF